L’homicide conjugal à Montréal, ses raisons, ses conditions et son déroulement - Cusson, Maurice; Boisvert, Raymonde (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1994)
Conjugal homicide is a situation where one person murders another person with whom he or she is involved through a matrimonial, quasi-matrimonial or other romantic relationship, the study of this type of homicide is based on the entirety of conjugal murders known to police (77) and committed in different municipalities on the island of Montreal during two time periods, namely 1954 to 1962 and 1985 to 1989. The great majority of these crimes are committed by a man onto a woman. Analyses show that possessiveness — understood to be the desire of one person to exclusively control the other — is by far the reason which leads a man to murder the woman he supposedly loves. However, this desire to possess or control is not in itself sufficient for a man to execute his criminal activity, since a number of conditions must coexist : the woman questions her relationship with the man ; the man may physically strike the woman ; the man has the advantage of greater physical strength; the period of time involved is sufficiently lengthy allowing the crisis to develop and enter its critical phase and finally, the perpetrator succeeds in surpassing the inhibitions which initially impede one from killing another.